The tension between person centred and task focused care in an acute surgical setting: A critical ethnography. Issue 1 (February 2018) - Sharp, Sandra; Mcallister, Margaret; Broadbent, Mark
Abstract: Problem: Person centred care is a key indicator of quality care and a policy direction in many hospitals yet some patients experience care that falls short of this standard. Background: Health services worldwide are prioritising the delivery of person centred in order to address historical concerns over patient safety and quality care and to improve workplace morale. Workplace culture is known to affect nurses' care giving. Question: This research aimed to uncover the cultural factors that hindered or facilitated the delivery of person centred care in an acute setting and answer the question: How does workplace culture influence nurses' delivery of person centred care? Methods: Critical ethnography provided the philosophical and methodological framework. Data were collected through participant observation, individual and focus group interviews, examination of care planning documents. Data were analysed hermeneutically and critically to make tacit cultural knowledge explicit and to suggest ways to reconstruct the culture of this specific nursing unit. Findings: Nurses organised their work in response to the urgency of the task at hand and nursing routines. People who received that care were rarely included in planning care. Discussion: Task focused ways of working can predominate in workplace cultures where an emphasis is placed on efficiency. Efficiency is part of the neoliberalist health care agenda and it stands in contrast to ideals of person-centred effectiveness because the latter may actually slow down procedures and require holistic approaches, rather than segmented care. Efficiency in this study appeared to be reinforced by an embedded and naturalised cultural practice amongst the nurses, which was to value fast-paced and completed tasks, because of the recognition it would receive from peers. Yet it also constituted a tension and bind for the nurses because the failure to be person-centred meant their professional values were unmet, and this led to moral distress and workplace dissatisfaction. If nurses were assisted to develop recognition of competing discourses in their work, and rationales to support a values-based practice, it is likely that they could be empowered to resist the status-quo and actually achieve the aspirations outlined in person-centred care rhetoric. Conclusion: Organisations and individuals striving for person-centred care need to develop awareness of the social and political forces that shape and constrain practice, in order to approach their work more consciously and critically.